Effects of Tax Reform on the Demand for Owner-Occupied Housing: A Micro Simulation Approach - David Brownstone; Peter Englund; Mats Persson (The Research Institute of Industrial Economics (IUI), 1984)
The paper analyzes the effects on the demand for owner-occupied housing that are likely to result from the Swedish 1983-85 tax reform. This is done by means of a micro-simulation model which takes into account the dichotomous nature of the demand for housing: the consumers choose the mode of tenure (owning versus renting) as well as the quantity of housing conditional on the choice of the mode of tenure. The tax reform consists of a general reduction of marginal tax rates (i.e. an increase in disposable income) together with limitations in the deductibility of mortgage interests. The simulations show that this will cause an increase in home-ownership in the sense that more households will demand owner occupied housing. At the same time, however, the households will demand smaller houses on the average, and thus aggregate demand for small and medium-sized units will increase while demand for large units will fall sharply.
Keywords: C60; D04; D10; O18; 330; Microsimulation; tax reform; owner-occupied housing